2023
DOI: 10.1111/risa.14195
|View full text |Cite
|
Sign up to set email alerts
|

Risk modelling of ESG (environmental, social, and governance), healthcare, and financial sectors

Abstract: Climate change poses enormous ecological, socio‐economic, health, and financial challenges. A novel extreme value theory is employed in this study to model the risk to environmental, social, and governance (ESG), healthcare, and financial sectors and assess their downside risk, extreme systemic risk, and extreme spillover risk. We use a rich set of global daily data of exchange‐traded funds (ETFs) from 1 July 1999 to 30 June 2022 in the case of healthcare and financial sectors and from 1 July 2007 to 30 June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Based on this logical reasoning, a mechanism framework of ESG rating influencing the value of enterprises is established in this paper, which includes three components: green technology innovation [45][46][47], internal control, and financing cost, as shown in Figure 1.…”
Section: Hypothesis 5: the Uncertainty Of Economic Policy Positively ...mentioning
confidence: 99%
“…Based on this logical reasoning, a mechanism framework of ESG rating influencing the value of enterprises is established in this paper, which includes three components: green technology innovation [45][46][47], internal control, and financing cost, as shown in Figure 1.…”
Section: Hypothesis 5: the Uncertainty Of Economic Policy Positively ...mentioning
confidence: 99%
“…Additionally, the family structure effect study conducted by Chaudhry et al (2023) has shown that the underprivileged communities are the most affected ones when it comes to juvenile delinquency, and not so much other families. The sense of direction and parental authority, and even more, the financial hardship, sometimes increase the proportion of delinquent behaviors that are involved by adolescents.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Research has proven that poorer youth, especially those experiencing poverty, are more likely to be in crime due to frustration and isolation (Malik et al, 2020). A country's cultural norms and values also play an essential role in classifying juvenile delinquency in Pakistan (Chaudhry, Chen, Ahmed, & Nasir, 2023;Malik et al, 2020). Family interaction, community assistance systems, and religion are other factors that further influence youth behaviors (Saeed, Khan, Gul, & Sadiq, 2017;Shahzad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%